2000
DOI: 10.1165/ajrcmb.22.6.3779
|View full text |Cite
|
Sign up to set email alerts
|

Lung Overexpression of the Vascular Endothelial Growth Factor Gene Induces Pulmonary Edema

Abstract: We hypothesized that the angiogenic mediator, vascular endothelial growth factor (VEGF), known to be expressed in the lung and to be capable of inducing local edema in skin, might evoke the development of lung edema if expressed in excess amounts. To test this hypothesis, we developed an in vivo model of VEGF overexpression in the lung on the basis of delivery to the respiratory epithelium of the VEGF165 complementary DNA by an E1(-) adenovirus vector (AdVEGF165). Administration of AdVEGF165 by the intratrache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
223
0
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(238 citation statements)
references
References 46 publications
(58 reference statements)
11
223
0
4
Order By: Relevance
“…Thus, a role for VEGF in the initial increase in endothelial permeability that characterises ARDS cannot be excluded. In keeping with this possibility, adenoviral-induced overexpression of VEGF in healthy animals is associated with increased oedema formation [19]. Interestingly, in the present study, VEGF immunolocalisation labelled alveolar inflammatory cells, in agreement with the finding by THICKETT et al [6], which demonstrated that VEGF was released by isolated inflammatory cells.…”
Section: Vascular Endothelial Growth Factor and Ards Y Abadie Et Alsupporting
confidence: 93%
“…Thus, a role for VEGF in the initial increase in endothelial permeability that characterises ARDS cannot be excluded. In keeping with this possibility, adenoviral-induced overexpression of VEGF in healthy animals is associated with increased oedema formation [19]. Interestingly, in the present study, VEGF immunolocalisation labelled alveolar inflammatory cells, in agreement with the finding by THICKETT et al [6], which demonstrated that VEGF was released by isolated inflammatory cells.…”
Section: Vascular Endothelial Growth Factor and Ards Y Abadie Et Alsupporting
confidence: 93%
“…15,16 Disruption of the alveolar-capillary membrane leads to flooding of the alveoli, causing disturbances in pulmonary mechanics and impairment of gas exchange. 17,18 Multiple investigators have confirmed the similarities in the stages and morphologic patterns of pulmonary oxygen toxicity in many animal species as well as man. 19 …”
Section: Introductionmentioning
confidence: 94%
“…The EB concentration was expressed as a percentage of the total dose of EB administered as described earlier. 16 …”
Section: Ebmentioning
confidence: 99%